The Empowering Effect of Embodied Awareness Practice on Body Structural Map and Sensorimotor Activity: The Case of Feldenkrais Method - Davide Crivelli; Massimilla Di Ruocco; Alessandra Balena; Michela Balconi (Brain Sciences, 2021)
While outcomes of embodied awareness practices in terms of improved posture and flexibility, movement efficiency, and well-being are often reported, systematic investigations of such training effects and of the actual nature, extent, and neurofunctional correlates of learning mechanisms thought to lie at the core of such practices are very limited. The present study focused on the Feldenkrais method (FM), one of the most established embodied awareness practices, and aimed at investigating the neurofunctional outcomes of the somatic learning process at the core of the method by testing the modulations induced by a standardized FM protocol on the complexity of practicers’ body structural map and on the activity of their sensorimotor network during different movement-related tasks (i.e., gestures observation, execution, and imagery). Twenty-five participants were randomly divided into an experimental group—which completed a 28-session FM protocol based on guided group practice—and a control group, and underwent pre-/post-training psychometric and electrophysiological assessment. Data analysis highlighted, at the end of the FM protocol, a significant increase of EEG markers of cortical activation (task-related mu desynchronization) in precentral regions during action observation and in central regions during action execution and imagery. Also, posterior regions of the sensorimotor network showed systematic activation during all the action-related tasks.